Pengaruh Komunikasi, Insentif, Dan Beban Kerja Terhadap Kepuasan Kerja Karyawan Pada PT. Dana Arta Mining (DAM) - Efan Kurniawan; Handayani, Susi; Kurniawan , Mohammad (JURNAL MANAJEMEN PENDIDIKAN, 2026)
This study aims to analyze the effect of communication, incentives, and workload on employee job satisfaction at PT. Dana Arta Mining (DAM). The research applies a quantitative descriptive approach to explain the relationships among variables based on numerical data. The population of this study consists of all 50 employees of PT. Dana Arta Mining (DAM), all of whom were included as research samples using a saturated sampling technique. Data were collected through Likert-scale questionnaires supported by observation and literature review. Data analysis was conducted using descriptive statistical analysis, validity and reliability tests, classical assumption tests, and multiple linear regression analysis with the assistance of SPSS version 26. The results indicate that partially, communication has a negative and insignificant effect on employee job satisfaction, while incentives and workload have a positive and significant effect. Simultaneously, communication, incentives, and workload have a significant influence on employee job satisfaction. This study is expected to provide practical implications for company management in improving employee job satisfaction through effective communication, fair incentive systems, and proportional workload management. Keywords: Communication, Incentives, Workload, Job Satisfaction, Employees